Management of Laryngeal Carcinoma - Harwood, Andrew R. (Revista Brasileira de Cancerologia, 2023)
Cancer of the larynx in North America is the commonest form of cancer of the head and neck region. In our own institution it accounts for one-quarter of all head and neck cancers. The purpose of this article is to review the management of this condition with particular emphasis on the relative roles of radiation and surgery.